Effect of tidal environment on the trophic balance of mixotrophic hexacorals using biochemical profile and photochemical performance as indicators. (April 2018) - Rosa, Inês C.; Rocha, Rui J.M.; Cruz, Igor; Lopes, Ana; Menezes, Natália; Bandarra, Narcisa; Kikuchi, Ruy; Serôdio, João; Soares, Amadeu M.V.M.; Rosa, Rui
Abstract: Fluctuations of environmental factors in intertidal habitats can disrupt the trophic balance of mixotrophic cnidarians. We investigated the effect of tidal environments (subtidal, tidal pools and emerged areas) on fatty acid (FA) content of Zoanthus sociatus and Siderastrea stellata . Effect on photophysiology was also accessed as an autotrophy proxy. There was a general tendency of a lower percentage of zooplankton-associated FAs in colonies from emerged areas or tidal pools when compared with colonies from the subtidal environment. Moreover, tidal environment significantly affected the photophysiology of both species. Colonies from the subtidal generally showed lower values of α, ETRmax and Ek when compared with their conspecifics from tidal pools or emerged areas. However, the absence of consistent patterns in F v / F m and in dinoflagellate-associated FAs, suggest that these corals are well adapted to intertidal conditions. This suggests that intertidal pressures may disturb the trophic balance, mainly by affecting heterotrophy of these species. Graphical abstract: Image 1 Highlights: Tidal environment affect the photophysiology of Z. sociatus and S. stellata . Emerged hexacorals presented lower percentage of zooplankton-associated FAs. Tidal environment affect the quality of ingested phytoplankton by hexacorals. Intertidal stressors disturb heterotrophy in mixotrophic hexacorals.